INTERPRETASI GEOKIMIA UNSUR UTAMA DAN JEJAK KOMPLEKS VOLKANIK GUNUNG PONGKOR KABUPATEN BOGOR, JAWA BARAT - -, Johanes Hutabarat (Bulletin of Scientific Contribution, 2006)
The research about study on geochemistry igneous rocks of Gunung Pongkor, Bogor, West Java. Basuki, et al., (1994) summarized the geology of the Pongkor areas consists of pyroclastic rocks (breccias and tuff) and lava flows and domes. Some problem to identifications which can in this research shall be as follows : How chemical composition and rocks afinity and also its evolution of exist in Mount Pongkor area have typical marking?.Samples of the Gunung Pongkor were extensively analyzed for major oxides and trace elements. Compositions of geochemical samples have been plotted and are used in drawing petrogenetic inferences. Igneous rocks Gunung Pongkor belong to the medium calc-alkalic to high Calc-alkalice suites (Peccerillo and Taylor; 1976), and have SiO2 contents in the range of 61,34-68,55%, middle and TiO2 and Al2O3 successively high (14,99-19,63%) and lower (< 0,50%); while K2O range from 1,90-2,55%. Other characteristic is the existence of some example of more enriched in Rb content and Ba. This Enrichment is also expressed by K2O content which relative higher. Than Ni element content and low Cr, and also Mg number ([Mg#]) less than 65, designate that its rock is not primitive, or equally experience of larger ones crystal fraksinasi from its mains magma.